PENGARUH LATIHAN DEPTH JUMP TERHADAP POWER OTOT TUNGKAI PEMAIN BOLA VOLI CLUB IVOSBA JUNIOR BENAI - Beni Andrika; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aim of this study was to determine the effect of the Depth Jump training on the explosive power of the limbs of Volosba Junior Benai Volleyball Club Players. The data obtained as a result of the research are the quantity data through tests before and after giving the treatment of the Deep Jump exercise. The data was obtained through tests and measurements from 8 Ivosba Junior Benai Volleyball Club athletes. The variables in this study are the Deep Jump Exercise symbolized by X as the independent variable, while the Leg Muscle Power is represented by Y as the dependent variable. Based on observations from researchers with Ivosba Junior Benai, the coach of Volleyball Club, researchers saw and noticed that they were technically good enough, this could be proven by their directional service and smash, but what became a problem when athletes were practicing or competing that the explosive power of muscles is missing the legs very much, when the ball is hit the jump is not optimal, which means that the ball often fails and does not attack. So researchers and trainers agreed to give a vertical jump test to discover the leg muscle power of Volleyball Club Ivosba Junior Benai players. The analysis was performed using the t-test, based on data analysis and discussion, it can be concluded that there was a significant impact of the Deep Jump training on the Volosba Junior Benai Volleyball Club Leg Muscle Power, as shown by a Thitung of 8.66 and a Ttabel of 1.895 at α= 0.05Key Words: Deep Jump